Simultaneous p53 and p16 Immunostaining for Molecular Subclassification of Head and Neck Squamous Cell Carcinomas - Pakkanen, Pihla; Silvoniemi, Antti; Aro, Katri; Bäck, Leif; Irjala, Heikki; Aaltonen, Leena-Maija; Hagström, Jaana; Haglund, Caj; Laine, Jukka; Minn, Heikki; Huvila, Jutta (SPRINGER, 2025)
Purpose
Our aim was to assess the ability of simultaneous immunohistochemical staining (IHC) for p16 and p53 to accurately subclassify head and neck squamous cell carcinomas (HNSCC) as HPV-associated (HPV-A) versus HPV-independent (HPV-I) and compare p53 IHC staining patterns to TP53 mutation status, p16 IHC positivity and HPV status.
Methods
We stained 31 HNSCCs for p53 and p16, and performed next-generation sequencing (FoundationOne (c) CDx) on all cases and HPV in-situ hybridization (ISH) when sufficient tissue was available (n = 23). p53 IHC staining patterns were assessed as wildtype (wt) or abnormal (abn) patterns i.e. overexpression, null or cytoplasmic staining.
Results
In a majority of cases (28/31) interpretation of p16 and p53 IHC was straightforward; 10 were considered HPV-A (p16+/p53wt) and 18 cases were HPV-I (p16-/p53abn). In the remaining three tumours the unusual immunophenotype was resolved by molecular testing, specifically (i) subclonal p16 staining and wild type p53 staining in a tumour positive for HPV and with no TP53 mutation (HPV-A), (ii) negative p16 and wild type p53 staining with a TP53 mutation and negative for HPV (HPV-I), and (iii) equivocally increased p16 staining with mutant pattern p53 expression, negative HPV ISH and with a TP53 mutation (HPV-I).
Conclusion
Performing p16 and p53 IHC staining simultaneously allows classification of most HNSCC as HPV-A (p16 +, p53 wild type (especially basal sparing or null-like HPV associated staining patterns, which were completely specific for HPV-A SCC) or HPV-I (p16 -, p53 mutant pattern expression), with the potential for limiting additional molecular HPV or mutational testing to selected cases only.